2014
DOI: 10.1111/j.2047-2927.2014.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Second to fourth digit ratio: a predictor of adult testicular volume

Abstract: SUMMARYIt has been suggested that second to fourth digit ratio (digit ratio) may correlate with male reproductive system function or disorders. This hypothesis is based on finding that the Hox genes control finger development and differentiation of the genital bud during embryogenesis. Thus, we investigated the association between digit ratio and adult testicular volume. A total of 172 Korean men (aged 20-69 years) hospitalized for urological surgery were prospectively enrolled. Patients with conditions known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
2
11
0
2
Order By: Relevance
“…This finding was similar to the previous studies about the relationship between digit ratio and adult sex hormone levels Bang et al, 2005;Muller et al, 2011;Oh et al, 2014). This finding was similar to the previous studies about the relationship between digit ratio and adult sex hormone levels Bang et al, 2005;Muller et al, 2011;Oh et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding was similar to the previous studies about the relationship between digit ratio and adult sex hormone levels Bang et al, 2005;Muller et al, 2011;Oh et al, 2014). This finding was similar to the previous studies about the relationship between digit ratio and adult sex hormone levels Bang et al, 2005;Muller et al, 2011;Oh et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Sex differences in digit ratios develop early in childhood and are unaffected by pubertal growth (McIntyre, 2006). In another study, Oh et al (2014) reported that men with a higher digit ratio may be more likely to have smaller testis volumes compared to those with a lower digit ratio. These developments led to the use of 2D : 4D as a tool of investigating possible associations between prenatal sex hormone exposure and various behaviors, diseases, and disorders.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indirect evaluation mechanisms are plausible. Under normal conditions, females could have used the male ornament and body size, which are positively correlated with internal reproductive organ size (Cotton et al., ; Rogers et al., ), as is the case in several other insect species (Bangham et al., ; Fairn, Schulte‐Hostedde, & Yves, ; Oh, Kim, Yoon, Kim, & Kim, ). But in our experimental design any information from male eyespan was explicitly constrained so that it could not serve as a proxy for male reproductive organ size (these traits were not correlated, Pearson ρ 183 = −0.031, p = .682).…”
Section: Discussionmentioning
confidence: 99%
“…And in our previous study, we found that anogenital distance, another indicator of prenatal androgenic exposure, was associated with the risk of prostate cancer (Sahin et al, ). Another study found that those with a higher 2D:4D finger ratio had lower testicular volumes than those with a lower 2D:4D finger ratio (Oh, Kim, Yoon, Kim, & Kim, ). In addition, there are studies suggesting that the finger ratio can predict adult penile size and that the effects of prenatal testosterone may partly explain the difference in adult penile size (Choi et al, ).…”
Section: Discussionmentioning
confidence: 99%